Perceived benefits of cochlear implants by parents: expectations, decision-making process, and barriers to care - Ateya Megahed Ibrahim; Abdel-H; Eman Wardany Abdelaal Mohamed; Nesrine Saad Farrag (SpringerOpen, 2023)
Abstract Background Identifying predictive factors of the cochlear implant outcomes in pediatric patients is critical in guiding tailored rehabilitation programs. The study aimed to assess cochlear implant outcomes, identify predictors, and highlight decision-making factors and barriers to quality care. Methods This cross-sectional study included parents of children who received unilateral cochlear implants for bilateral severe- to- deep sensorineural hearing loss. Inclusion criteria were age ≤ 5 years and intelligence quotient (IQ) Scores ≥ 85, A pre-designed structured questionnaire was used to collect data from parents/guardians of the children attending follow-up. The Arabic validated Glasgow Children Benefit Inventory score was used to assess the health-related quality of life (QOL) after intervention. Results The quality of life (QOL) score (outcome) after surgery was positive in all cases. Multivariate analysis showed that the site of operation (Bahtim hospital and Ain Shams Hospital [AOR(95% confidence interval CI), 5.7 (1.4-23), 5 (1.4-17.9), p = 0.015, 0.013, respectively]), education of the father (university/postgraduate [AOR (95% CI): 5 (1.4-17.9), p = 0.013]), the parents' expectation that their child would be able to participate in regular classroom activities [AOR (95% CI): 8.9 (3.7-21.3), p < 0.001], and history of Attention deficit/hyperactivity disorder (ADHD), perinatal hypoxia, and low birth weight [AOR (95% CI): 2.5 (1.2-5.1), 3.7 (1.7-8.1), 4.7 (2.1-10.5), p = 0.013, 0.001, ≤ 0.001, respectively] are significant independent predictors of good outcome. Conclusion All parents expressed a positive change in their child's QOL. Almost all parents of children with cochlear implants face many barriers in obtaining quality healthcare services for their children. Parents, especially those with lower schooling, should receive good counselling to increase their confidence in their children's capabilities and maximize benefits of regular follow-up. Improving the quality of healthcare centers is recommended.